Excessive Iodine Promotes Pyroptosis of Thyroid Follicular Epithelial Cells in Hashimoto's Thyroiditis Through the ROS-NF-κB-NLRP3 Pathway - Liu, Jiameng; Mao, Chaoming; Dong, Liyang; Kang, Ping; Ding, Chao; Zheng, Tingting; Wang, Xuefeng; Xiao, Yichuan (Frontiers in Endocrinology, 2019)
The occurrence of the autoimmune thyroid disease Hashimoto’s thyroiditis (HT) has increased in recent years, and increasing evidence proven the effects of excessive iodine intake on thyroid disease. In this study, we examined the status of pyrptosis in thyroid tissues obtained from patients with HT and the effects of excessive iodine on the pyroptosis of thyroid follicular cells (TFCs) in an attempt to expound the effects of excessive iodine on HT pathological development. Our results showed that increased pyroptosis occurred in the thyroid tissues of HT patients, and an increase of ptroptosis activity in TFCs was primed by excessive iodine in vitro. The process is mediated by reactive oxygen species (ROS) and activation of the NF-κB signaling pathway. In addition, excessive iodine also induced NLRP3 inflammasome activation of TFCs, which promoted pyroptosis in TFCs. Moreover, the release of interleukin-1β (IL-1β) is closely linked with pyroptosis activation. Taken together, our results demonstrated that excessive iodine contributed to aberrant pyroptosis activation in TFCs, which could be a pivotal predisposing factor for HT development.